The relationship between active drag and swimming velocity during front-crawl swimming - Narita, K.; Ogita, F.; Nakashima, M.; Gonjo, T.; Takagi, H. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to investigate the relationship between active drag and swimming velocity during front-crawl swimming using the MRT-method (a methodology using the measured values of residual thrust) and the MAD-system with the same group of swimmers. Six male swimmers swam front-crawl with (Whole stroke: WS) and without leg motion (arms-only stroke: AS) in the MRT-method, and they swam only AS trials in the MAD-system. In the AS trials, swimmers were instructed to put a buoy between their thighs and their ankles were tighten with a band. To establish an individual equation for calculating drag, it was assumed that drag can be expressed as D = kVb (D: drag, V: velocity). For both MAD and MRT testing, trials were conducted using a wide range of swimming velocities (between 0.9 and 1.5 m/s). The drag/velocity data were fitted to the equation to obtain coefficient k and degree b for each swimmer, and the active drag for 1.0, 1.2 and 1.4 m/s were calculated using the function with individual k and b. In the AS condition, active drag in the MRT-method was larger than that in the MAD-system at all velocities. In the MRT-method, we found no difference between WS and AS, meaning that the kicking motion did not increase or decrease the drag. The difference in drag between the MRT-method and the MAD-system might be due to differences in the propelling condition (pushing fixed pads and the water) that potentially affect the flow around the body.